Demand for Vacations /Travel in Protected Areas – Dimension of Tourists' Ecological Behavior - Rodica Minciu; Mihaela Pădurean; Delia Popescu; Remus Hornoiu (Amfiteatru Economic Journal, 2012)
Tourism, in itself, is one of the main users of the environment and, implicitly, an important contributor to its deterioration. Intensification of tourist travel will naturally generate an increase of the negative environmental impacts and, in the long term, a decline in tourism development opportunities. In this context, more and more emphasis is placed on finding and promoting low environmental impact forms of travel, including eco-tourism, rural tourism, tourism in protected areas, cultural tourism, adventure tourism, etc., at the same time on encouraging, inciting potential tourists to consume these categories of products (holidays). Globally conducted studies have revealed a good understanding of and an increasing receptivity to sustainable forms of travel among tourists. Nevertheless, the place they hold in the structure of tourist circulation is still modest, mainly due to the insufficient supply, in its turn determined by ignorance of the demand and by the additional requirements the consumer of such holidays has to meet, especially in regard to behavior. In line with these developments and trends, this study aimed to identify the behavior of tourists in protected areas and its determinants, to encourage a responsible attitude towards the environment and its quality. For this purpose, desk and field researches were made to allow the characterization of holiday request in protected areas and to formulate proposals regarding tourists' education.
Keywords: Q26; Q27; Q56; 330; tourist demand; protected areas; ecological behavior; ecotourism; sustainable tourism development; eco(logical) tourism products